Countdown - Patterson, James, 1947-; DuBois, Brendan (Little, Brown, and Company, 2023)
"Agent Amy Cornwall excels at working from the shadows--until a botched field operation reveals dark dealings between her bosses and an informant. And a hidden plot by a terrorist genius that could kill thousands of Americans. Among them: her husband and daughter. She has to go dark. The Division wants to erase her. And they know every detail about her identity, her history, and her family. Agent Cornwall's countdown has begun"--